Thermomechanical simulation and experimental characterisation of hot tearing during solidification of aluminium alloys. (April 2013) - He, Y; Li, S; Sadayappan, K; Apelian, D
Abstract : Casting experiments were conducted to characterise hot tearing in two aluminium alloys (A356 and M206) using an instrumented constrained permanent mould. The thermal history, thermal contraction and the tensile force induced by thermal contraction were monitored during the casting process. The thermal stress was modelled by considering the contact between the solidified metal and the mould. The calculated displacement and tensile load were compared to measured data and reasonably good agreement was observed. Hot tearing tendency of these two aluminium alloys was predicted using a strain based hot tearing model. It was found that M206 not only demonstrated much higher hot tearing tendency than A356, but also the vulnerable locations for hot tearing were different from A356. The predicted hot tearing positions coincide well with those observed in the castings. The effects of mould temperature, mould material and pouring temperature on the susceptibility of hot tearing were also investigated.